Pengaruh Faktor Keuangan Dan Karakteristik Pemerintah Daerah Terhadap Financial Distress - Yoli Wulandari; Fefri Indra Arza (Universitas Negeri Padang, 2020)
This study aims to determine the effect of Financial Factors (Effectiveness Ratios, Efficiency Ratios, And Growth Ratios) and Local Government Characteristics (Financial Independence Of Local Governments, Population, Area, And Audit Opinion) on the Financial Distress on the Districts/ Cities in West Sumatra Province in 2016-2018. The data in this study use secondary from BPK and BPS. The sampling technique uses a total sampling method with a total sample of 19 districts / cities wtih a period of time of 4 years. Analysis of the data using binary logistic regression analysis. The results of this study indicate that (1) ratio of effectiveness has a negative and not significant effect on financial distress, (2) Efficiency ratio has a positive and not significant effect on financial distress, (3) growth ratio has a positive and not significant effect on financial distress, (4) The financial independence of local governments has a negative and not significant effect on financial distress, (5) population has a negative and significant effect on financial distress, (6) Area has a positive and significant effect on financial distress, (7) Audit opinion has a negative and not significant effect on financial distress.